PENGAWETAN SEPULUH JENIS KAYU IRIAN JAYA SECARA DIFUSI - Sasa Abdurrohim; Abdurahim Martawijaya (Jurnal Penelitian Hasil Hutan, 1987)
The result of dip diffusion treatment  of ten wood species from lrian Jaya is reported in this paper. The wood species comprised  among others wafut (Cananga odorata Hook.f.  et Th.), starka (Octomeles sumatrana Miq.), senai (Dracontomelon mangiferum Bl.), sutiet (Spondias cytherea Sonn.), bemoe (Canarium indicum L.), raja (Pterygota forbesii F.v.Muell), sehiega (Celtis latifolia Planch.), sehiye (Sterculia macrophylla Vent.), susu (Alstonia scholaris R.Br.), and bimiek (Pterocymbium beccarii K. Schum.).  Particular  attention is directed to penetration  and retention requirement/or wood uses under roof and outdoor without soil contact. Solution concentration of BFCA preservative used was 30 percent.Among ten wood species tested, only one species (sehye) could not be treated by dip diffusion process in 30 percent solution, because retention requirement for  use under roof without soil contact (condition A) could not be reached.  Two of the remaining nine wood species which could be treated by dip diffusion process and hence fulfilling the requirement for uses under condition B were raja and sehiega woods.Storage phase proposed for bemoe, raja and sehiega wood is 8 weeks, while for six other wood species ( wafut, stark a, senai,  sutiet, susu and bimiek) is 4 weeks.During storage phase, severe attack of blue-stain on seven wood species  were observed, while the remaining three species which were not affected were senai, sehiega and bimiek wood. An addition of anti blue-stain compound in the preservative  is recommended